Deskripsi Penerapan Kaidah Konsumsi Islami Menurut Al-Haritsi Pada Anggota Paguyuban Cak dan Ning Surabaya 2015 - Andrew Hermawan; Fatin Fadhilah Hasib (Universitas Airlangga, 2017)
The aim of this research is to describe the behavior of the member of Cak dan Ning Surabaya association in 2015 based on the Islamic consumption behavior theory Al-Haritsi, namely, syari’ah rules, quantity rules, social rules and environmental rules. This study is using descriptive qualitative participative approach to conduct the goals. The units of the analysis in this study are the rule of syari’ah rules, quantity rules, social rules and environmental rules. There are three informants involved in this study who are also the members of the association of Cak and Ning Surabaya 2015. Data triangulation technique is used to ascertain the quality and consistency of data. The technique of analysis which is used is qualitative data analysis according to Miles and Huberman. The results showed that members of the association have implemented syari’ah rules, also apply most of the rules of quantity, social norms, and implementing environmental rules.